A concept of dual-responsive prodrugs based on oligomerization-controlled reactivity of ester groups: an improvement of cancer cells versus neutrophils selectivity of camptothecin - Klemt, Insa; Reshetnikov, Viktor; Dutta, Subrata; Bila, Galyna; Bilyy, Rostyslav; Cuartero, Itziar Cossío; Hidalgo, Andrés; Wünsche, Adrian; Böhm, Maximilian; Wondrak, Marit; Kunz-Schughart, Leoni A.; Tietze, Rainer; et al. (RSC Medicinal Chemistry, 2024)
Many known chemotherapeutic anticancer agents exhibit neutropenia as a dose-limiting side effect. In this paper we suggest a prodrug concept solving this problem for camptothecin (HO-cpt). The prodrug is programmed according to Boolean “AND” logic. In the absence of H2O2 (trigger T1), e.g. in the majority of normal cells, it exists as an inactive oligomer. In cancer cells and in primed neutrophils (high H2O2), the oligomer is disrupted forming intermediate (inactive) lipophilic cationic species. These are accumulated in mitochondria (Mit) of cancer cells, where they are activated by hydrolysis at mitochondrial pH 8 (trigger T2) with formation of camptothecin. In contrast, the intermediates remain stable in neutrophils lacking Mit and therefore a source of T2. In this paper we demonstrated a proof-of-concept. Our prodrug exhibits antitumor activity both in vitro and in vivo, but is not toxic to normal cell and neutrophils in contrast to known single trigger prodrugs and the parent drug HO-cpt.
CRIS-Team Scopus Importer:2024-04-19

Fluorogenic, catalytic, photochemical reaction for amplified detection of nucleic acids - Dutta, Subrata; Fülöp, Annabelle; Mokhir, Andriy (Bioconjugate Chemistry, 2013)
Photochemical, nucleic acid-induced reactions, which are controlled by nontoxic red light, are well-suited for detection of nucleic acids in live cells, since they do not require any additives and can be spatially and temporally regulated. We have recently described the first reaction of this type, in which a phenylselenyl derivative of thymidine (5′-PhSeT-ODNa) is cleaved in the presence of singlet oxygen (Fülöp, A., Peng, X., Greenberg, M. M., Mokhir, A. (2010) A nucleic acid directed, red light-induced chemical reaction. Chem. Commun. 46, 5659-5661). The latter reagent is produced upon exposure of a photosensitizer 3′-PS-ODNb (PS = Indium(III)- pyropheophorbide-a-chloride: InPPa) to >630 nm light. In 2012 we reported on a fluorogenic version of this reaction (Dutta, S., Flottmann, B., Heilemann, M., Mokhir, A. (2012) Hybridization and reaction-based, fluorogenic nucleic acid probes. Chem. Commun. 47, 9664-9666), which is potentially applicable for the detection of nucleic acids in cells. Unfortunately, its yield does not exceed 25% and no catalytic turnover could be observed in the presence of substrate excess. This problem occurs due to the efficient, competing oxidation of the substrate containing an electron rich carbon-carbon double bonds (SCH=CHS) in the presence of singlet oxygen with formation of a noncleavable product (SCH=CHSO). Herein we describe a related, but substantially improved photochemical, catalytic transformation of a fluorogenic, organic substrate, which consists of 9,10-dialkoxyanthracene linked to fluorescein, with formation of a bright fluorescent dye. In highly dilute solution this reaction occurs only in the presence of a nucleic acid template. We developed three types of such a reaction and demonstrated that they are high yielding and generate over 7.7 catalytic turnovers, are sensitive to single mismatches in nucleic acid targets, and can be applied for determination of both the amount of nucleic acids and potentially their localization. © 2013 American Chemical Society.

Nucleic acid-specific photoactivation of oligodeoxyribonucleotides labeled with deuterated dihydro-N, N, N′, N′-tetramethylrhodamine using green light - Schikora, Margot; Dutta, Subrata; Mokhir, Andriy (Histochemistry and Cell Biology, 2014)
We developed a simple protocol for high-yielding synthesis of conjugates of a deuterated dihydro-N, N, N′, N′-tetramethylrhodamine (F*) with oligodeoxyribonucleotides and a 2′-OMe RNA (a representative nuclease-resistant, chemically modified oligonucleotide) using easily accessible starting materials including NaBD and conjugates of oligonucleotides with N, N, N′, N′-tetramethylrhodamine (F). These compounds were found to be stable in air and insensitive to light at 525, 635 and 650 nm, whereas slow activation occurs upon their exposure to 470 nm light. However, at the conditions of the templated reaction, in the presence of a target nucleic acid and a photocatalyst based on the eosin structure, the F* is oxidized forming fluorescent F. This reaction is >30-fold faster than the background reaction in the absence of the template. Moreover, the presence of a single mismatch in the target nucleic acid slows down the templated reaction by eightfold. These activatable dyes can potentially find applications as nucleic acid-specific probes for super-resolution imaging in live cells. © 2014 Springer-Verlag Berlin Heidelberg.

Red light-triggered photoreduction on a nucleic acid template - Dutta, Subrata; Rühle, Jennifer; Schikora, Margot; Deussner-Helfmann, Nina S.; Heilemann, Mike; Zatsepin, Timofei; Duchstein, Patrick; Zahn, Dirk; Knoer, Guenther; Mokhir, Andriy (Chemical Communications, 2020)
Conjugate Sn(iv)(pyropheophorbide a)dichloride-(peptide nucleic acid) catalyzes reduction of azobenzene derivatives in the presence of complementary nucleic acid (NA) upon irridiation with red light (660 nm). This is the first red light-induced NA-templated photoreduction. It is highly sensitive to single mismatches in the NA-template and can detect down to 5 nM NAs.
CRIS-Team Scopus Importer:2020-09-11